AKTIVITAS AMILASE, LIPASE, DAN PROTEASE PADA DIET SERAT PANGAN: VARIASI PH DAN LAMA PEREBUSAN - Leny Yuanita, ; Suzana Surodjo, ; Wiwik Yuliastuti, (Matematika dan Sains, 2011)
The research objective: to describe the influence of variation of pH and boiling time on the activities of digestive enzymes. This research used Post Test only Control Group Design, which observed variables were the enzymes activities of amylase, protease, and lipase both in duodenum and pancreas. In vivo study using 54 Rattus norvegicus, Wistar strain. The treatment animals were divided into 8 groups treatment feeding and 1 group standard feeding. The treatment feeding was a diet with high fiber of long yard beans with variation of pH (3 and 7) and boiling time (0, 5, 20, 35 min). After the treatment period of 48 days, data were analyzed through inferential statistics ( = 0.05). Results showed that pH and boiling time affect on the enzymes activities of amylase, protease, and lipase both in duodenum and pancreas. At high fiber dietary of long yard beans, increasing pH and boiling time treatments, resulting the lowest decreasing digestive enzymes activities. All feeding treatments yielded the lower enzymes activities compare with the standard diet, except the activity of the pancreatic amylase on the treatment of pH 7 20 min or 35 min, and duodenum lipase on pH 3- 35 min of boiling time. The highest enzymes activities in the duodenum and pancreas were on the pH 7 - 35 min of boiling time treatment.